2004
DOI: 10.1583/04-1386r.1
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Transplantation of Autologous Skeletal Myoblasts in Postinfarction Patients With Severe Left Ventricular Dysfunction

Abstract: Transcatheter transplantation of autologous skeletal myoblasts for severe left ventricular dysfunction in postinfarction patients is feasible, safe, and promising. Scrutiny with randomized, double-blinded, multicenter trials appears warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 47 publications
(54 reference statements)
2
29
0
1
Order By: Relevance
“…Experimentally, myoblasts engraft in postinfarction scars, differentiate into myotubes, and improve LV function (reviewed in Dowell et al 1 ). The consistency and robustness of these results have paved the way for the first surgical [2][3][4][5][6] or catheter-based [7][8][9] phase I trials, which have confirmed feasibility but by virtue of design could not fully evaluate efficacy and safety profiles. We therefore implemented the Myoblast Autologous Grafting in Ischemic Cardiomyopathy (MAGIC) trial to specifically address these issues.…”
mentioning
confidence: 99%
“…Experimentally, myoblasts engraft in postinfarction scars, differentiate into myotubes, and improve LV function (reviewed in Dowell et al 1 ). The consistency and robustness of these results have paved the way for the first surgical [2][3][4][5][6] or catheter-based [7][8][9] phase I trials, which have confirmed feasibility but by virtue of design could not fully evaluate efficacy and safety profiles. We therefore implemented the Myoblast Autologous Grafting in Ischemic Cardiomyopathy (MAGIC) trial to specifically address these issues.…”
mentioning
confidence: 99%
“…Also, in vivo experiments in rats showed the same cell-dose dependency [78]. In patients, although some cases of arrhythmias have been reported, overall, an improvement in the cardiac function together with an increase in the viability and perfusion has been found in most of the clinical trials published so far [79] [76] [80][81][82][83][84][85]. Some studies like that published by Gavira et al have been successful with no cardiac arrhythmia reported after one-year follow-up [80].…”
Section: Clinical Trials Using Skeletal Myoblastsmentioning
confidence: 82%
“…Although some trials failed to demonstrate a significant increase in cardiac function after cell transplantation when compared with controls, several other randomized trials showed measurable improvements that were comparable to established therapeutic regimes (Reffelmann et al, 2009). Nonrandomized, smaller-scale trials also produced variable results, ranging from no significant changes in left ventricular ejection fraction to a significant improvement, of up to a 14% increase, during the follow-up period (Strauer et al, 2002;Perin et al, 2004;Fernandez-Aviles et al, 2004;Ince et al, 2004;Strauer et al, 2005;Katritsis et al, 2005;Bartunek et al, 2005;Mocini et al, 2006;Gavira et al, 2006;Ahmadi et al, 2007;Choi et al, 2007;Klein et al, 2007;Li et al, 2007;Stamm et al, 2007;Tatsumi et al, 2007).…”
Section: Clinical Studiesmentioning
confidence: 99%